A Discourse of General Principles of Good Governance in Public Services in Indonesia - Umami, Farida; Maududi, Ahkam Nashrullah; Mahmudah, Aminah Rizqi (Faculty of Law, Universitas Negeri Semarang, 2022)
Public service is one of the commitments in government administration. Good, measurable, and humane public services have a significant impact on the impetus for accelerated development. However, negative issues in public services, especially in Indonesia, are still often encountered, ranging from issues of bribery, corruption, abuse of authority, to discrimination in the implementation of public services. This study aims to analyze the general principles of good governance (AAUPB) in the delivery of public services in Indonesia. Using the study approach of law, constitution, and Pancasila, this study confirms and finds that the implementation of AAUPB in public services includes several things ranging from transparency, community participation, efficiency, and aspects of convenience.